Pembuatan Asam Asetat dari Air Kelapa Secara Fermentasi Kontinyu Menggunakan Kolom Bio-Oksidasi (Kajian dari Tinggi Partikel dalam Kolom dan Kecepatan Aerasi) - Nurika, Irnia; Hidayat, Nur (Jurnal Teknologi Pertanian, 2001)
Acetic acid is a one of industrial product that large consumed in Indonesia. Acetic acid can make from a substrate, which consist of ethanol. It could make from many kind of material such as fruits, pineapple leather, coffee pulp, and coconut water. The large quantity of coconut water, more than 900 million litters per year in Indonesia is an unused potency in a maximum way. This study was observed the used of bioâoxidation column technique in order to increase the efficiency of acetic acid production which made from coconut water. In addition, this study was also conducted to identify the rate of aeration process, the height of the particle column and its interaction on the way to perform the acetic acid. This study was preformatted using factorial randomized block design, consisting of two factors, each factor consist of three levels from the combination of its interaction and the experiment was in duplicate. The first factor was the height of particle column i.e 16 cm, 25 cm, 34 cm and the second one was aeration rate i.e 0.06 vvm, 0.07 vvm, 0.08 vvm. The parameters measured were the production of acetic acid and the alcohol. The result showed that the average of acetic acid production is 0.44 â 12% per day and the alcohol, which consumed by microorganism, is 2.14 â 2.73 ml per day, which the capabilityÂ  to produce the acetic acid is 21.79 â 55.10 mg per hour. Â  Keywords: acetic acid, bio-oxidation column technique, coconut water